2010
DOI: 10.1161/strokeaha.109.577742
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism and Risk of Ischemic Stroke in Young Adults

Abstract: Background and Purpose-Case reports or case series have reported the association between hyperthyroidism and cerebrovascular disease. However, hyperthyroidism has never been considered as a potential risk factor for stroke in young people. The aim of the present study is to estimate the risk for ischemic stroke among hyperthyroidism patients aged 18 to 44 years during a 5-year period after the diagnosis of hyperthyroidism as compared to a cohort of patients without hyperthyroidism during the same period. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 29 publications
(35 reference statements)
0
83
1
2
Order By: Relevance
“…Moreover, as death is the final outcome, all studies show the right temporality. In contrast, as hyperthyroidism has been associated with a number of potentially lethal conditions such as structural changes in the heart (32), thromboembolic episodes (4,5), and cardiac arrhythmias (3), the relation between hyperthyroidism and mortality is biologically plausible but clearly nonspecific. As described in case reports, severe hyperthyroidism, as seen in thyrotoxic crisis, can be lethal (33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as death is the final outcome, all studies show the right temporality. In contrast, as hyperthyroidism has been associated with a number of potentially lethal conditions such as structural changes in the heart (32), thromboembolic episodes (4,5), and cardiac arrhythmias (3), the relation between hyperthyroidism and mortality is biologically plausible but clearly nonspecific. As described in case reports, severe hyperthyroidism, as seen in thyrotoxic crisis, can be lethal (33).…”
Section: Discussionmentioning
confidence: 99%
“…This raises hyperthyroidism not RAI, as hyperthyroidism has many established vascular effects such as hypercoagulopathy (5), increased risk of atrial fibrillation (AF), increased left ventricular ejection fraction and heart failure (6). The theory that it is the hyperthyroidism per se that holds the risk is supported by Sheu et al (7), who demonstrated an increased risk of stroke among hyperthyroid treated with anti-thyroid medicine. However, other studies of hyperthyroid patients treated with RAI, surgery and/or medical treatment have described a relationship between hyperthyroidism and cardiac -but not cerebrovascular mortality or morbidity (8,9,10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The database was created by the Taiwan National Health Research Institute (NHRI) using a systematic sampling method to randomly select a representative sample of all enrollees. There were no statistically significant differences in demographic characteristics, including age, gender, and distribution between the sample and original populations (11). Because the LHID 2005 dataset consisted of de-identified and secondary data released to the public for research, the study was exempted from full review by the Institutional Review Board of Taipei Medical University.…”
Section: Databasementioning
confidence: 99%